A method to nourished beach stability assessment: The case of China. (1st July 2019) - Liu, Gen; Cai, Feng; Qi, Hongshuai; Zhu, Jun; Lei, Gang; Cao, Huimei; Zheng, Jixiang
Abstract: Beach nourishment is an effective method for maintaining shoreline position, and it has been preferred to restore beaches in China. However, in the post-nourishment assessment, there are only some single-indicator models ( e.g. beach durability, sediment loss rate) which could not fully reflect the actual performance of a nourished beach. This study presents a multiple-indicator model of nourished beach stability assessment, aiming at quantitatively assessing the physical performance of nourished beaches. Geomorphic factors affecting the physical performance of nourished beaches were analyzed and summarized through critical review of literature. An indicator system for assessing the stability of nourished beaches was established by integrating oceanographic parameter ( i.e. wave energy, storm intensity, and storm frequency), design parameter ( i.e. beach length, grain size, volume density, beach planform, and beach protection structure) and adaptability parameter ( i.e. intertidal width, dry beach width, and erosional hot spot). Based on data collecting, each indicator was graded into five classes from 1 to 5, and the associated weight of each indicator was given by the method of variation coefficient. Finally, a multi-indicator and indicator-weighted assessment model for the stability of nourished beaches was established and a new index called Nourished Beach Stability Index (NBSI) was proposed. The physical performances of sixteen nourished beaches representative of China were then quantitatively assessed. The results showed this assessment model could better assess the physical performance of nourished beaches than the single-indicator assessment models for taking beach's characteristics into account. The results can help scientists and managers make appropriate management strategies. This multiple-indicator assessment model can be used to both quantitatively assess the actually physical performance of the beach nourishment projects and to choose the design scheme from multiple alternatives for beach nourishment project. Highlights: An indicator system for assessing the stability of nourished beaches is proposed. A multi-indicator assessment model with weighted indicators is proposed. This assessment model can be used to quantify the physical performance of beach nourishment projects.